"xp^2+2yp+x = 0\\\\\n2y = -xp - \\dfrac{x}{p}\\\\\n2\\dfrac{dy}{dx} = -p -\\dfrac{1}{p} -x\\dfrac{dp}{dx}+\\dfrac{x}{p^2}\\dfrac{dp}{dx}\\\\\n\\dfrac{3p^2+1}{p} = \\dfrac{x(1-p^2)}{p^2}\\dfrac{dp}{dx}\\\\\n \\dfrac{(1-p^2)}{p(3p^2+1)}dp = \\dfrac{dx}{x}\\\\\n\\int \\dfrac{(1-p^2)}{p(3p^2+1)}dp =\\int \\dfrac{dx}{x}\\\\\nlnp -\\dfrac{2}{3}ln(3p^2+1) = lnx\\\\\n\\dfrac{p}{\\sqrt[3]{9p^4+6p^2+1}} = x\\\\\n9x^3p^4-p^3+6x^3p^2+x^3=0"
is an implicit solution of the question because it is impossible to express p straightforward in terms of y.
Comments
Leave a comment